A new species of the genus Promacrolaelaps (Acari: Laelapidae) associated with Propomacrus bimucronatus (Pallas) (Coleoptera: Scarabaeidae) in Iran - Joharchi, Omid; Halliday, Bruce; Beyzavi, Gholamreza (Zootaxa, 2013)
We describe a new species of mite from Iran - Promacrolaelaps propomacrus sp. nov. (Acari: Laelapidae). The new spe-cies was collected in association with the beetle Propomacrus bimucronatus (Pallas) (Coleoptera: Scarabaeidae: Euchiri-nae) in holes in the trunk of oak trees. The genus Promacrolaelaps is redescribed and distinguished from the related genus Hypoaspis Canestrini sens. strict.